TINDAK TUTUR ILOKUSI DALAM NEGOSIASI UPACARA MEMINANG (KAJIAN ETNOGRAFI KOMUNIKASI) - Andi Marta, Redo (Universitas Ahmad Dahlan, 2017)
The study proposes marriage ceremony backdrop for their negotiations with language Minangkabau. Negotiations in this study aims to explain the culture of oral tradition in particular illocutionary speech act. This research uses a qualitative approach with methods of ethnography of communication. Illocutionary speech acts research results that found three of the five types of speech act speech act. The three types of illocutionary speech acts found in the form of speech acts assertive, directive, and expressive. Assertive speech acts found be stating a fact or truth of something. Directive speech acts found be sent (request), justifying, and asking permission to others. Expressive speech acts found be thanked.